Composition Tailoring via N and S Co‐doping and Structure Tuning by Constructing Hierarchical Pores: Metal‐Free Catalysts for High‐Performance Electrochemical Reduction of CO2. Issue 47 (25th October 2018) - Yang, Hengpan; Wu, Yu; Lin, Qing; Fan, Liangdong; Chai, Xiaoyan; Zhang, Qianling; Liu, Jianhong; He, Chuanxin; Lin, Zhiqun
Abstract: A facile route to scalable production of N and S co‐doped, hierarchically porous carbon nanofiber (NSHCF) membranes (ca. 400 cm 2 membrane in a single process) is reported. As‐synthesized NSHCF membranes are flexible and free‐standing, allowing their direct use as cathodes for efficient electrochemical CO2 reduction reaction (CO2 RR). Notably, CO with 94 % Faradaic efficiency and −103 mA cm −2 current density are readily achieved with only about 1.2 mg catalyst loading, which are among the best results ever obtained by metal‐free CO2 RR catalysts. On the basis of control experiments and DFT calculations, such outstanding CO Faradaic efficiency can be attributed to the co‐doped pyridinic N and carbon‐bonded S atoms, which effectively decrease the Gibbs free energy of key *COOH intermediate. Furthermore, hierarchically porous structures of NSHCF membranes impart a much higher density of accessible active sites for CO2 RR, leading to the ultra‐high current density. Abstract : An effective method was developed for scalable production of N, S co‐doped hierarchically porous carbon nanofiber membranes. These membranes are flexible and self‐supporting, and they could be directly used as a cathode for electrochemical CO2 reduction. With a circa 1.2 mg catalyst loading, a 94 % Faradaic efficiency and −103 mA cm −2 current density was obtained, which are among the best results for metal‐free CO2 RR catalysts.